Therapeutic indications for sinonasal topical steroid treatment and its effects on eosinophilic chronic rhinosinusitis after endoscopic sinus surgery. Issue 10 (23rd October 2021) - Saito, T; Okazaki, K; Hamada, Y; Hashimoto, K; Tsuzuki, K
Abstract: Objective: This study evaluated the post-operative indications for sinonasal topical steroid treatment using a corticosteroid (steroid)-eluting, sinus-bioabsorbable device and its effects in patients with eosinophilic chronic rhinosinusitis. Method: Post-operative courses were investigated in two groups: group A with patients who underwent sinonasal topical steroid treatment, and group B with control patients who did not. Results: Group A was significantly younger than group B ( p < 0.01), and the pre-operative computed tomography score was significantly higher in group A than in group B ( p < 0.05). In the post-operative stage, the nasal symptoms questionnaire component of olfactory loss and the post-operative endoscopic appearance score were significantly worse in group A than in group B ( p < 0.01). Conclusion: These data suggest that younger age, more severe rhinosinusitis and post-operative olfactory loss led to the need for sinonasal topical steroid treatment to prevent relapsing inflammation after functional endoscopic sinus surgery in patients with eosinophilic chronic rhinosinusitis.